2002
DOI: 10.1007/s00221-002-1039-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of N-methyl-D-aspartate receptor-mediated excitatory postsynaptic potentials in the neostriatum after methamphetamine sensitization

Abstract: It has been suggested that behavioral methamphetamine sensitization involves changes in cortical excitatory synaptic inputs to neostriatal (Str) projection neurons. To test this, we performed blind whole-cell recording of medium spiny neurons in Str slice preparations. In Str neurons of naive rats, the amplitude of the subcortical white matter stimulation-induced N-methyl- D-aspartate receptor-mediated excitatory postsynaptic potentials (NMDA-EPSPs) was decreased upon hyperpolarization, owing to the voltage-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 37 publications
5
18
0
Order By: Relevance
“…However, longterm withdrawal (7 days) did result in a markedly potentiated neurotoxic response to NMDA exposure, a finding that is consistent with the electrophysiological findings of Moriguchi et al (2002). Long-term withdrawal does appear to be an essential component of the observed neurotoxicity, since short-term withdrawal and chronic exposure without withdrawal did not result in a potentiated NMDA effect.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…However, longterm withdrawal (7 days) did result in a markedly potentiated neurotoxic response to NMDA exposure, a finding that is consistent with the electrophysiological findings of Moriguchi et al (2002). Long-term withdrawal does appear to be an essential component of the observed neurotoxicity, since short-term withdrawal and chronic exposure without withdrawal did not result in a potentiated NMDA effect.…”
Section: Discussionsupporting
confidence: 84%
“…Long-term NMDA receptor antagonism by METH may result in neuronal excitability during withdrawal. In fact, Moriguchi et al (2002) reported increased amplitudes of NMDA mediated excitatory postsynaptic potentials (EPSPs) in neostriatal slices following withdrawal from METH. Evidence of neuronal excitability during protracted METH withdrawal suggests that compensatory responses to chronic METH administration may be similar to other NMDA antagonists.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations